2003
DOI: 10.1017/s0144686x03001259
|View full text |Cite
|
Sign up to set email alerts
|

‘Making the best of things’: relatives' experiences of decisions about care-home entry

Abstract: Despite the growing awareness of the significance of helping a relative to relocate to a care home as a key phase in the care-giving career, relatively few British studies have explored this experience in depth. Informed by a constructivist perspective, this study sought a better understanding of nursing home placements from the viewpoint of relatives. Data were collected in 37 semi-structured interviews involving 48 people who had assisted a close relative to move

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
110
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(113 citation statements)
references
References 40 publications
1
110
1
1
Order By: Relevance
“…Indeed, several participants indicated that the research interview was the first time they had discussed their feelings. The participants in this study felt that they were under pressure, had inadequate information, felt that things were out of their control and that they were working in opposition to health and social care staff (Davies & Nolan, 2003).…”
Section: Theoretical Models Of Caring Transitionsmentioning
confidence: 99%
See 4 more Smart Citations
“…Indeed, several participants indicated that the research interview was the first time they had discussed their feelings. The participants in this study felt that they were under pressure, had inadequate information, felt that things were out of their control and that they were working in opposition to health and social care staff (Davies & Nolan, 2003).…”
Section: Theoretical Models Of Caring Transitionsmentioning
confidence: 99%
“…These distinct stages were 'making the best of it' , 'making the move' and 'making it better' . Davies & Nolan (2003) found that in more than half of the cases (i.e. 19 cases or more) it was the primary carer who had to make the final decision in relation to placement.…”
Section: Theoretical Models Of Caring Transitionsmentioning
confidence: 99%
See 3 more Smart Citations